STRATEGI PENINGKATAN RETRIBUSI PASAR YOUTEFA SEBAGAI SALAH SATU SUMBER PENDAPATAN ASLI DAERAH DI KOTA JAYAPURA - BEDES, WASTI APRILLIA; LENGKONG, FLORENCE; TAMPI, GUSTAAF BUDDY (Sam Ratulangi University, 2019)
To realize regional capability and independence and strengthen the structure of regional revenues, thecontribution of locally generated revenue in the state expenditure bedget structure must always be improvedbecause it is one of the benchmarks of capability and a mirror of regional independence. Market retributionis an important source of regional income in addition to resources. other income that has a strategic role inthe framework of financing regional development so that the increase in research market retribution usesan interactive analysis model and SWOT analysis. Therefore, the research is the Strategy for IncreasingYoutefa's Market Retribution as One of the Sources of Local Revenue in the City of Jayapura.This study uses Qualitative Research Methods using SWOT analysis techniques. Analysis of internal factorsproduces factors of strength and weakness. Strengths (Strenghts), namely the Authority / Authority grantedby the City Government, Training for improvement of Human Resources (HR), Retribution collectionprocedures, Making facilities for traders, Clarity of mandate of youtefa market organizations. Weaknessfactors are low formal education, low financial ability to meet the budget, low compassion competency, lackof functional education, weak supervision and law enforcement functions. External factors produceopportunities and threats. Opportunities are the legal foundation for managing market retribution, goodeconomic growth, increasing community income, community education. Threat Factors (Thrreats), namelythe involvement of many parties in determining retribution rates, Weak law enforcement, Inadequateinfrastructure and facilities, low levels when the government pays the market. Based on a SWOT analysis,ten strategies.Keywords: Strategy, Market Retribution, Regional Original Income.